miRNA Enriched in Human Neuroblast Nuclei Bind the MAZ Transcription Factor and Their Precursors Contain the MAZ Consensus Motif - Goldie, Belinda J.; Fitzsimmons, Chantel; Weidenhofer, Judith; Atkins, Joshua R.; Wang, Dan O.; Cairns, Murray J. (Frontiers in Molecular Neuroscience, 2017)
While the cytoplasmic function of microRNA (miRNA) as post-transcriptional regulators of mRNA has been the subject of significant research effort, their activity in the nucleus is less well characterised. Here we use a human neuronal cell model to show that some mature miRNA are preferentially enriched in the nucleus. These molecules were predominantly primate specific and contained a sequence motif with homology to the consensus MAZ transcription factor-binding element. Precursor miRNA containing this motif were shown to have affinity for MAZ protein in nuclear extract. We then used Ago1/2 RIP-Seq to explore nuclear miRNA-associated mRNA targets. Interestingly, the genes for Ago2-associated transcripts were also significantly enriched with MAZ binding sites and neural function, whereas Ago1-transcripts were associated with general metabolic processes and localized with Sc35 spliceosomes. These findings suggest the MAZ transcription factor is associated with miRNA in the nucleus and may influence the regulation of neuronal development through Ago2-associated miRNA induced silencing complexes (miRISC). The MAZ transcription factor may therefore be important for organizing higher order integration of transcriptional and posttranscriptional processes in primate neurons.